Trends in participation, sex differences and age of peak performance in time-limited ultramarathon events: a secular analysis - Thuany, M.; Gomes, T. N.; Villiger, E.; Weiss, K.; Scheer, V.; Nikolaidis, P. T.; Knechtle, B. (Medicina, 2022)
Background and Objectives: Increases in the number of participants in time-limited ultra-marathons have been reported. However, no information is available regarding the trends in participation, performance and age in 12 h and 24 h time-limited events. The aim of the study was to describe the trends in runners` participation, performance and age in 12 h and 24 h ultra-marathons for both sexes and to identify the age of peak performance, taking into account the ranking position and age categories.